2012
DOI: 10.1016/j.eurpsy.2010.04.011
|View full text |Cite
|
Sign up to set email alerts
|

The association between Internet addiction and psychiatric disorder: A review of the literature

Abstract: Internet addiction is a newly emergent disorder. It has been found to be associated with a variety of psychiatric disorders. Information about such coexisting psychiatric disorders is essential to understand the mechanism of Internet addiction. In this review, we have recruited articles mentioning coexisting psychiatric disorders of Internet addiction from the PubMed database as at November 3, 2009. We describe the updated results for such disorders of Internet addiction, which include substance use disorder, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

44
562
4
58

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 753 publications
(668 citation statements)
references
References 62 publications
44
562
4
58
Order By: Relevance
“…Similar findings come from recent studies linking symptoms of mental ill health, depression and anxiety to problematic mobile phone use (Augner and Hacker 2012;Ha et al 2008;Yen et al 2009), to problematic internet use (Kaess et al 2014;Ko et al 2012) and to amount of mobile phone use which is expected to partly reflect problematic use (Ikeda and Nakamura 2014;Thomée et al 2011). Similar to these studies, our cross-sectional study cannot clarify the direction of these associations.…”
Section: Hrqol and Problematic Mobile Phone Usesupporting
confidence: 72%
See 1 more Smart Citation
“…Similar findings come from recent studies linking symptoms of mental ill health, depression and anxiety to problematic mobile phone use (Augner and Hacker 2012;Ha et al 2008;Yen et al 2009), to problematic internet use (Kaess et al 2014;Ko et al 2012) and to amount of mobile phone use which is expected to partly reflect problematic use (Ikeda and Nakamura 2014;Thomée et al 2011). Similar to these studies, our cross-sectional study cannot clarify the direction of these associations.…”
Section: Hrqol and Problematic Mobile Phone Usesupporting
confidence: 72%
“…Previous studies found hyperactivity and ADHD associated with problematic internet use (Kaess et al 2014;Ko et al 2012;Kormas et al 2011;Ozturk et al 2013) and using the mobile phone for entertainment (playing games, internet) (Byun et al 2013b;Zheng et al 2014). Hyperactive adolescents are easily distracted, show problems in sustaining attention and are less capable of impulse control (Douglas 1972).…”
Section: Behaviour and Problematic Mobile Phone Usementioning
confidence: 99%
“…In this study, BAI, BDI, and CASS were set as mediator variables. Ko et al 21 reported that IAD was associated with ADHD, major depressive disorder, and social anxiety disorder. It was, however, a descriptive review that lacked statistical analyses to support such associations.…”
Section: Beck Depression Inventory the Beck Depression Inventory (Bdi)mentioning
confidence: 99%
“…Furthermore, research on the association between IAD and aggressive behaviors could not confirm the causal relationship up to now. 21 Thus, the primary aim of this study was to identify the causal relationships between IAD and aggression, and the secondary aim was to investigate the associations of IAD and aggression with comorbid clinical phenomena such as depression, anxiety, and ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies measuring independent risk factors for addiction revealed that it is associated with being male, [13], being a heavy user [14,15], relationship dissatisfaction [16], depression [14,15] and anxiety [15]. In addition, recent studies have shown ADHD is the most frequent comorbid disorder with Internet addiction (also in FB addiction), and the severity of ADHD is associated with the severity of Internet addiction [17,18].…”
Section: Introductionmentioning
confidence: 99%